Quinone-Mediated Microbial Goethite Reduction and Transformation of Redox Mediator, Anthraquinone-2, 6-Disulfonate (AQDS). Issue 1 (2nd January 2017) - Zhu, Weihuang; Yu, Dan; Shi, Mengran; Zhang, Yongtao; Huang, Tinglin
ABSTRACT: The aim of current study is to identify the kinetic characteristics and elucidate the possible transformation pathways of the interaction between the redox mediator (anthraquinone-2, 6-disulfonate, AQDS) and goethite during the process of microbial goethite reduction by Shewanella putrefaciens, a dissimilatory iron reduction bacterium (DIRB). Speciations of both AQDS and microbially reduced ferrous iron are used to characterize the interaction process among S. putrefaciens, AQDS and goethite. Due to the complexities of the natural environment, two pre-incubation reaction systems of the "DIRB–goethite" and the "DIRB–AQDS" are introduced to investigate the dynamics of goethite reduction and redox transformation of AQDS. Results show that the characteristics of the microbial goethite reduction and the kinetic transformation between two species of the redox mediator are different in two pre-incubation reaction systems. Both abiotic and enzymatic reactions and their coupling regulate the kinetic process for "redox mediatoriron" interaction in the presence of DIRB. This study will help to understand the characteristics and mechanism of microbial reduction of the Fe(III) oxide and transformation of redox mediator.